La Inteligencia emocional e intención de emprendimiento en los estudiantes universitarios en la Carrera de Administración en la Universidad Técnica de Cotopaxi - Zambrano Loja, Carlos Manuel (2022)
Since a decade ago, entrepreneurship has become the fundamental pillar for developing countries, in the same way, business management has undergone substantial changes that go hand in hand with the evolution of the human being and technological innovation, these changes have contributed to financial improvement in the countries and with the development of new products and services The research shows that emotional intelligence is a determining factor for the start of an enterprise, in the same way there are investigations that highlight that to undertake there are psychological aspects that must be evaluated, in the same way cognitive factors must be considered, and others Studies have shown that entrepreneurs have certain characteristics of their own and can intervene in the entrepreneurial process.